Sub-Versões na Urbe: uma cartografia decolonial do graffiti em João Pessoa - Cunha, Thiago da Silveira (2024)
This thesis takes a decolonial look at the history of graffiti and pixação, with the central objective of creating cartography based on the production of two artists working in Paraíba: Subitus and Cyber. From the perspectives of Quijano (2005), Segato (2012), Mignolo (2019), Krenak (2022), Fanon (2020) among others, we understand that one of the decolonial tasks is to recognize colonial patterns of power that perpetuate relations of exploitation and colonialist violence. The search is for a decentralization of attention, perceiving - and seeking - new gnosis and narratives in the symbolic construction of reality. Cartography is deepened as a method - a path - capable of opening the mnemonic way taken by Cyber memories, in the downtown, connecting spaces and generations of the local cultural and artistic movement. Based on the approach of Illares (2018) and Mignolo (2019) regarding the Guatemalan artist's production named Bevenuto Chavajay, and on the reflections of bell hooks (2020), we point out decolonial art as a process of healing and cure. Product of the action of a border consciousness that recognized the colonial differences. Decolonial aesthetics that seeks to confront colonial patterns of power, but above all to reconnect with the territory and its ways of knowing and feeling. The notion of “amefricanity” (GONZALEZ, 1988) and expressive violence (SEGATO, 2012) are used to take a new look at the main memory regimes that make up the graffiti movement. In this context, artistic expressions are mobilized in order to create meanings and affections that delegitimize colonialist narratives.